Complications of curative radiation treatment for early prostate cancer. Issue 5 (16th January 2018) - James, Melissa; McLean, Gabrielle; Williams, Stephen; Robinson, Bridget; Yi, Ma
Abstract: Aim: To report the incidence of urological complications following curative radiation treatment for early prostate cancer, including minimally invasive urological procedures (MUIP), hospital admissions and open surgical procedures. Second malignancies following radiation are also reported and compared with patients undergoing a prostatectomy. Methods: Included were patients receiving curative intent external beam radiation treatment for early prostate cancer between January 1, 2002, and December 31, 2009. Medical records were reviewed for baseline characteristics, treatment details and outcomes. Kaplan–Meier methods were used to derive the 5‐year cumulative incidence of the urological outcomes and second malignancy. Results: There were 439 patients identified. The median follow‐up was 6.96 years. The median age was 69. A total of 56 patients developed a radiation related urological complication, 25 requiring hospital admission. The 5‐year cumulative incidence for an MIUP and admission was 3.95% (95% confidence interval (CI), 2.47–6.28) and 2.24% (95% CI, 1.17–4.27), respectively. There were no open surgical procedures. Further malignancy developed in 27 patients during the 5‐ to 9‐year posttreatment period with a cumulative incidence of 10.7% (95% CI, 7.31–15.51). Of the comparator prostatectomy group, of the 265 eligible patients analyzed, 19 patients developed a second malignancy with a cumulative incidence of 9.92% (95% CI, 6.28–15.48). On log‐rank testing, there was no difference in the cumulative incidence rates of second malignancy between 5 and 9 years, following respective treatments ( P   =  0.8554). Conclusions: The incidence of MUIP, hospital admissions and open surgical procedures following radiation is reassuringly low. The second malignancy rates are also low and similar to the rates in patients treated with a prostatectomy.